The secret of the key - Malone, Marianne (Malone, Marianne. Sixty-eight rooms adventure, 2015)
In the Art Institute of Chicago's miniature Thorne Rooms, the Thorne Rooms key and a mysterious set of rings lead Ruthie and Jack to new historical eras and a woman who went missing as a young girl.